The sports infrastructure and development of Brgy. Ugong, Pasig City and its role in the sports participation of its high school students - Bulusan, Nicole Anne B. 2000-
In a country full of concrete basketball courts, the popularity of other sports has risen in the Philippines in recent years and the youth are eager to try them but to be able to participate in sports, the participants must have the facilities or infrastructure in order to play. In this study, the researcher focuses on how these existing facilities shape the sports participation of the high school students of Brgy. Ugong , Pasig City. The aim of the study is to explore how the existing infrastructure, specifically its accessibility and viability in catering their endeavors, shapes the sports participation of the high school students. Findings from this research can enlighten Pasig City, Brgy. Ugong, and other city governments and barangay officials on the importance of including sports in their sports infrastructure and development efforts to cater to the overall quality of life of their citizens. In line with this, having accessible sports facilities allows sports to be cultivated by the participation of its citizens in diverse sports activities. These findings can also highlight the sporting potential of Filipinos in competitive sports locally and internationally if given the right facilities that cater to sporting activities